Supporting Society through Science - Balmonte, John Paul (Archīum Ateneo, 2023)
Science should serve to improve people’s lives through knowledge acquisition, education, and policy implementation. However, if rooted in exclusive and extractive practices, it can inadvertently elicit mistrust in various sectors in our society. Critical examination of historical foundations and current events in the Philippines, as demonstrated in thearticles in this special issue, helps identify problems that perpetuate—as well as solutions that break down—the divide between science and society. Valuing and incorporating perspectives from the public ensures that the nature and pace of progress in the Philippines are constantly well aligned with its people and their interests.KEYWORDS: SCIENCE-BASED REGULATIONS • COLONIAL INFLUENCES • SUSTAINABILITY • PROGRESSIVE FUTURES